Relocation of government activities as a regional policy measure - Johanna Yliskylä-Peuralahti (European Regional Science Association (ERSA), 2003)
In recent years there has been a growing interest towards relocation of government activities - moving civil service jobs away from capital to provincial regions, so from center to more peripheral regions - in Finland. Similar plans were made in the 1960s and 1970s, but they remained largely unimplemented. The aim of this paper is to examine the theoretical origins of these older relocation plans and to assess relocation of government activities as a tool in Finnish regional policy. Consideration is given to potential weak points and reasons behind the non-implementation of the relocation plans.
Keywords: 330